Arento Group in Spain : towards a sustainable future - Geoffroy, Paula Arellano, (SAGE Business Cases., 2019)
The Arento Group case examines how an agricultural business tries to make the transition towards higher levels of sustainability. Arento Group, based in the Zaragoza region in Spain, is slowly but surely adopting sustainable innovation practices and projects such as diverfarming entering the international market and upgrading the ecological production. With the new president coming to the office, Arento Group's new vision is set-to become more sustainable in all aspects (economic, social, and environmental) and expand business in foreign markets. Arento was already doing well in some areas but needed improvement in others. In order to realize intentions into actions, the group has to first identify the areas that require improvement and then decide on what changes have to be made across the whole value chain so the company can make the transition to higher levels of sustainability.